The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/09638280701427386
|View full text |Cite
|
Sign up to set email alerts
|

The experience of men using an upper limb prosthesis following amputation: Positive coping and minimizing feeling different

Abstract: The findings offer a greater psychological insight into adjustment from an upper limb amputation and the role of prostheses. These findings have implications for both the clinical rehabilitation of patients who undergo upper limb amputations, as well as for future research into the use and value of prostheses in facilitating the adjustment to this experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(155 citation statements)
references
References 33 publications
4
139
0
2
Order By: Relevance
“…Third, as highlighted in previous studies, having a prosthesis appears to reduce the distance between current and former selves and to minimize the perceived difference from others [9,41]. In particular, with its normal appearance, the M seemed to facilitate social interactions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, as highlighted in previous studies, having a prosthesis appears to reduce the distance between current and former selves and to minimize the perceived difference from others [9,41]. In particular, with its normal appearance, the M seemed to facilitate social interactions.…”
Section: Discussionmentioning
confidence: 97%
“…As such, they can potentially address both functional [3] and cosmetic [4] user needs and have positive psychosocial implications [5][6][7][8][9]. However, the actual impact of these technologies on patients' lives has been documented in only two case reports [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, all but one of the men with an upper limb prosthesis in Saradjian et al's [19] study were married or co-habiting. It seems that the experiences of young, single women have still received very little consideration.…”
mentioning
confidence: 99%
“…Yet the impact of amputation is much broader than physical functioning (for example, effects on body image and psychosocial adjustment [13][14][15]. Furthermore, Nauert [16] notes that much of the limited research into experiences of living with an amputation has focused on male participants, reflecting the higher incidence of amputation amongst men than women [17][18][19]. Women with disabilities, such as those with amputations, often report feeling stigmatized and consistently under pressure to conform to society's idea of the conventional woman, and stereotypical notions of female physique and beauty [9,20].…”
mentioning
confidence: 99%
“…While a full description of each of the study types and designs is beyond the scope of this article, representative goals of each of these types of studies are shown in the Table. User studies to understand the needs and preferences of prosthetic users or predictors of prosthetic use and abandonment are typically observational studies that involve surveys of users [41][42][43][44][45][46][47] and providers [48], medical record abstraction [47,49], focus groups [10], or in-person interviews [50]. User studies are typically recommended as the first step in product development research [10].…”
Section: Other Types Of Prosthetics Researchmentioning
confidence: 99%